Global Expansion Strategies of Russian Oil Companies: The Case of Lukoil - Sidyakin, Vladimir (2007)
Since the collapse of the former Soviet Union, tremendous changes and developments have taken place in the new Russian Federation as well as its relationship with other countries. Among all, performance and growth of Russian corporations has been phenomenal. Russian outward foreign direct investments have grown rapidly during the past few years. The natural-resource based companies have been the main drivers of the international growth of the Russian economy. It is expected that their performance will increase at an accelerating rate in the years to come, especially when Russian Federation become a member of the World Trade Organisation (WTO) in the near future. This study focuses on Russian Multinational corporations internationalisation process, particularly Russian oil industry. Nevertheless Russia has quite a few large oil companies the particular attention would be given to LUKOIL GROUP which is one of the most outstanding and biggest Russian oil companies and its current internationalisation strategy raised hot discussion. The current dissertation seeks to find the reasons behind internationalisation of Russian oil companies on the example of Lukoil, the environment selection and entry modes applied by oil companies.